Pathogenic mechanisms of autoantibodies: antibodies to intracellular and membrane-bound antigens - Andrade, Luís Eduardo Coelho (Henry Stewart Talks, 2020)
Autoantibodies targeting cell membrane-bound antigens, Autoantibodies targeting intracellular antigens, Autoantibodies as a result of damage to target tissues, Autoantibodies preceding the clinical onset of diseases, Pathogenic autoantibodies in rheumatology, neurology, dermatology and nephrology